A meta-analysis of acute alcohol use and the risk of suicide attempt - Borges, Guilherme (Psychol Med, 2016)
BACKGROUND: While there are reviews reporting on the prevalence of acute use of alcohol (AUA) prior to suicide attempts, no review has used a meta-analytic approach to estimate common odds ratios (OR) of the effect of AUA on suicide attempts. We aim to report the results of the first meta-analysis of controlled epidemiological studies on acute alcohol use and suicide attempt. METHODS: The English language literature on Medline, PsychInfo, Google Scholar, and public-use databases was searched for original articles and critical review reports on acute alcohol use and suicide attempt for the period ranging from 1996–2015. Studies had to report an OR estimate for this association. Common odds ratios and 95% Confidence Intervals (95%CI) from random effects in meta-analyses for any acute alcohol use and 2 levels of alcohol use on suicide attempt were calculated. RESULTS: We gathered 7 studies that provided OR estimates for the likelihood of suicide attempt by acute alcohol use, compared to those who did not drink alcohol. Studies used case-control (3) and case-crossover design (4). All studies found increased ORs for acute alcohol use on suicide attempt. Meta-analysis revealed a common OR of 6.97 (95%CI=4.77, 10.17) for any acute alcohol use. Evidence from 4 studies suggests that «low levels of acute drinking» resulted in an OR of 2.71 (95%CI=1.56, 4.71) and «high levels» had much greater odds of suicide attempt, OR of 37.18 (95%CI=17.38, 79.53). CONCLUSIONS: Acute use of alcohol is associated with increased likelihood of a suicide attempt, particularly at high doses. Such data should be incorporated into estimates of the burden of disease associated with alcohol use, which are currently limited by a consideration of only alcohol’s chronic effects. Future research should focus on the mechanisms through which acute use of alcohol confers risk for attempt.